ANALISIS KEBUTUHAN PENGEMBANGAN SOAL CERITA BERBASIS PRODUCTIVE STRUGGLE PADA MATERI BANGUN DATAR DI SEKOLAH DASAR - Meydi Rizky Miyajitima; Muhammad Rijal Wahid Muharram; Erwin Rahayu Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics instruction in elementary school is crucial because it lays the foundation for later stages of education. Its primary aim is to help students understand and apply mathematical concepts in az flexible, accurate, efficient, and precise manner when solving problems. Students are also expected to use reasoning to recognize patterns, formulate generalizations, and construct and explain mathematical proofs. Problem‑solving skills remain a central focus, encompassing the ability to understand problems, design and solve mathematical models, and interpret the resulting solutions. Additionally, students must be able to communicate mathematical ideas through symbols, tables, diagrams, or other media. Mathematics learning further seeks to cultivate positive attitudes—curiosity, perseverance, interest in learning, and self‑confidence—toward mathematics. This study aims to bridge gaps and address existing challenges by developing productive‑struggle‑based word problems on the topic of plane figures in elementary school. Such problems are intended not only to help students solve word problems about plane figures but also to deepen their conceptual understanding of the mathematics involved. The research adopts the 4D development model—Define, Design, Develop, and Disseminate. Preliminary studies through observation, interviews, and literature reviews indicate that teaching mathematics on plane‑figure material still encounters several obstacles: limited instructional resources, students’ difficulty managing gadget use (which can affect memory), and teachers’ struggles to engage students who have reading difficulties. The proposed word problems are expected to stimulate students’ critical thinking in everyday contexts and to enhance the productive effort they invest. Teacher support remains vital for enabling students to solve the word problems independently.